Penerapan Kaidah Penyiaran di Stasiun D’Radio Jambi - Yonathan K.M; Syarifuddin; Mardalina; Sururuddin (Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2019)
Radio development in Jambi City is very tight so it takes the ability to keep listeners listening to broadcasts. Radio broadcasters are the spearhead in a program that must be able to entertain and exist but still prioritize the applicable broadcasting rules. This study tries to describe the application of radio broadcasting rules at D'Radio Jambi station. The study used qualitative methods through observation, interviews, and documentation. Based on data analysis, the application of broadcasting rules by broadcaster D'Radio Jambi on the D'Viral entertainment broadcast program has been implemented well. The main broadcaster plays an important role in the success of the D'Viral program by the way it broadcasts. Entertaining and applying some broadcast rules such as Talk to one person, quality of speech, and mastery of vocabulary. Obstacles that are still faced are conveying messages, vocal technique constraints, broadcasters' ability constraints, and obstacles to knowing listeners. In general, some of the solutions that broadcasters do to overcome these obstacles are conducting broadcasting training, preparing broadcasts before broadcasting, and taking foreign language courses.